2018
DOI: 10.1161/jaha.118.009543
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Risk of Cancer: A Danish Population‐Based Cohort Study

Abstract: BackgroundAtrial fibrillation (AF) and cancer are frequent diseases worldwide. The timewise association between the diagnosis of AF and a subsequent diagnosis of cancer may clarify whether a mutual cause exists, and may also guide clinicians about time windows of high risk of cancer occurrence.Methods and ResultsWe conducted a population‐based cohort study among 26 222 men and 28 879 women free of AF and cancer at baseline based on the Danish Diet, Cancer and Health study. The participants were followed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 34 publications
7
47
0
2
Order By: Relevance
“…We provided an approach to interpret the data from mechanistic studies based on the microbiome. The microbiome features revealed a close association of AF with neurodegenerative diseases as well as cancers, which was supported by prior studies showing that AF had a correlation with AD and PD [40,41], and AF patients had relatively higher risks of several cancers, including lung cancer and CRC [42,50]. We also observed that the microbiome features of SLE and CML were highly similar.…”
Section: Discussionsupporting
confidence: 87%
“…We provided an approach to interpret the data from mechanistic studies based on the microbiome. The microbiome features revealed a close association of AF with neurodegenerative diseases as well as cancers, which was supported by prior studies showing that AF had a correlation with AD and PD [40,41], and AF patients had relatively higher risks of several cancers, including lung cancer and CRC [42,50]. We also observed that the microbiome features of SLE and CML were highly similar.…”
Section: Discussionsupporting
confidence: 87%
“…We provide an approach to interpret the data from mechanistic studies based on microbiome. The microbiome features revealed a close association of AF with neurodegenerative diseases as well as cancers, which was supported by prior studies showing that AF had correlation with AD and PD 52, 53 , and AF patients had relatively higher risks of several cancers including lung cancer and CRC 54, 64 . We also observed that microbiome features of SLE and CML were highly similar.…”
Section: Discussionsupporting
confidence: 75%
“…Frequent visits to the medical system for AF would increase the chance of early detection of cancer. Vinter et al 13 reported that NOAF is closely associated with metastatic cancer within 90 days in the same year, further supporting the concept that patients with NOAF may be accompanied by occult cancers. (2) Atrial natriuretic peptide (ANP) related to AF has been shown to have extensive anti-proliferative effects, and might account for the significant reduction in cancer incidence after 90 days.…”
Section: Discussionmentioning
confidence: 75%
“…Six published observational articles were incorporated into the present analysis. [9][10][11][12][13][14] The integrated result demonstrated that patients with NOAF have a 24% increased risk of developing cancer. The subgroup analysis stratified by time interval, gender and type of cancer revealed the following: (1) the incident cancer significantly increased within 90 days after NOAF diagnosis, but not after that; (2) males appeared to have a higher risk, when compared to females; (3) the risk of lung cancer, but not colorectal cancer or breast cancer, was higher in patients with NOAF, when compared to non-AF patients.…”
Section: Discussionmentioning
confidence: 99%